Design and development of DTV array antennas - Zou, Shang (2016)
This project is to study, design, develop and test array antennas for DTV based passive radar applications. Firstly, is to design a single DTV antenna that satisfy specific requirement. Then do the simulation, fabrication and measurement of a real antenna. And thus compare the simulated and measured results of the single DTV element. The differences would also be analysed. Secondly, duplicate the single DTV antenna to a four-element array antenna. In this project, the single antenna has been duplicated in 2 ways. One is along x-axis, the other one is along y-axis. After the design, simulation would also be done. Then fabricate the array antennas, take the measured results and analyse them, compare them with simalted results. Thirdly, Compare the results of a single DTV antenna and DTV array antennas. To study how does array antennas improve the performance of DTV antenna. All the simulated and measured results, and comparison conclusion will be included in this report.